O vínculo como estratégia de comunicação marcária : um olhar sobre a relação entre marcas e consumidores na contemporaneidade - Coelho, Débora Ferreira (2014)
In a communication context that changes constantly, it becomes ever timelier the searching for a theoretical study which offers subsidies on the relationship between brands and consumers in postmodernity. Thus, the primary objective of this research is to understand in which aspects the involvement of consumers with brands can be boosted by developing a relationship tie as a brand communication strategy. On this dynamic scenario we seek to understand - through the analysis of the Coca-Cola campaign for Coca-Cola Zero product, titled Descubra a sua Coca-Cola Zero with the theme Quanto mais você, melhor - the manifestations of contemporary practices for building brand communication strategies which emphasizes the relationship among people by a brand. For such investigative adventure we chose to adopt the assumptions of Comprehensive Sociology offered by Michel Maffesoli and Complexity by Edgar Morin.